A review of recent progress and developments in China smart cities. Issue 4 (30th November 2021) - Shan, Zhiguang; Zhang, Yanqiang; Zhang, Yaqi; Tang, Sisi; Wang, Wei
Abstract: Since 2008, the development of China's smarter cities has experienced four phases: Exploration and practice phase, normative adjustment phase, strategic breakthrough phase and all‐round development phase. A number of innovative practices such as the city brain and 'unified online government service' have provided the world with Chinese solutions for smart city construction. This study explains the concept and connotation of innovative smarter cities, summarizes the development status of China's innovative smarter cities, analyses and judges the seven development trends in the construction of innovative smarter cities, analyses the shortcomings and deficiencies, and puts forward policy suggestions to promote the development. It has an important reference value for comprehensively understanding the development concept and overall development status of China's innovative smarter cities and clarifying the next development direction.